2009
DOI: 10.1007/s00704-009-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface air warming in northeast China, with emphasis on the impacts of urbanization

Abstract: Based on homogenized land surface air temperature (SAT) data (derived from China Homogenized Historical Temperature (CHHT) 1.0), the warming trends over Northeast China are detected in this paper, and the impacts of urban heat islands (UHIs) evaluated. Results show that this region is undergoing rapid warming: the trends of annual mean minimum temperature (MMIT), mean temperature (MT), and mean maximum temperature (MMAT) are 0.40 C decade-1, 0.32 C decade-1, and 0.23 C decade-1, respectively. Regional average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 26 publications
4
42
0
5
Order By: Relevance
“…2), which indicates that R-2 effectively captured the intraseasonal and interannual variability of the observations. However, the correlation coefficients for Tmax are generally larger than those for Tmin, indicating that R-2 to some extent do not well assimilate the surface information, particularly that related to urban conditions because the urbanization effect is observed more apparently in Tmin (e.g., Li et al 2010;Ren and Zhou 2014). Therefore, the OMR trend should primarily reflect the impact of urbanization and other changes in land use, as was proposed by Kalnay and Cai (2003).…”
Section: Trends In 1979-2008mentioning
confidence: 96%
“…2), which indicates that R-2 effectively captured the intraseasonal and interannual variability of the observations. However, the correlation coefficients for Tmax are generally larger than those for Tmin, indicating that R-2 to some extent do not well assimilate the surface information, particularly that related to urban conditions because the urbanization effect is observed more apparently in Tmin (e.g., Li et al 2010;Ren and Zhou 2014). Therefore, the OMR trend should primarily reflect the impact of urbanization and other changes in land use, as was proposed by Kalnay and Cai (2003).…”
Section: Trends In 1979-2008mentioning
confidence: 96%
“…In general, such a classification utilizes either population data [6][7][8][9][10][11][12][13][14][15][16][17] or satellite data (such as nighttime light imagery and land cover dataset) [18][19][20][21][22][23] as well as the geographic location of the stations. In addition, Empirical Orthogonal Function (EOF) [24,25], Principal Component Analysis (PCA) [26,27] and station metadata [28] can also be applied to define reference or rural stations. By comparing the difference between urban and reference (rural) stations, the impact of urbanization on SAT can be estimated.…”
mentioning
confidence: 99%
“…Meanwhile, the climatic effect of urbanization has drawn more and more attention. Some previous studies indicated that urbanization has little impact on regional warming [7,13,26,27]. However, recent investigations have suggested that the urbanization process can not only increase the local daily temperature, but also play an essential role in regional climate change [6,9,12,[14][15][16][17][20][21][22][23][24][28][29][30]35,36].…”
mentioning
confidence: 99%
“…Climate change monitoring and simulation rely on reliable and extensive historical meteorological observations (Hanesiak John and Wang 2005;Jones et al 2008;Li et al 2010;Si et al 2012Si et al , 2014. However, most long-time climate records do not adequately represent climate change characteristics because of changes in instrumentation, observation methods, station relocation, and other non-climate factors; these changes result in a distortion in climate change monitoring (Aguilar et al 2003;Jiang et al 2010).…”
Section: Introductionmentioning
confidence: 99%